View On Science and Education (VOSE): Studi Terhadap Mahasiswa Program S1 IPA-Fisika - Mukhayyarotin Niswati Rodliyatul Jauhariyah; Khaerus Syahidi; Eti Sukadi; Wirawan Fadly (Kappa Journal, 2020)
This study aims to examine the concept of the nature of science (NOS) and attitudes towards teaching the NOS. The research used the View on Science Education (VOSE) instrument that was  developed by Chen (valid and reliable) which online distributed to students of Physics Education Program from Surabaya State University and IKIP PGRI Pontianak, as well as students of Science Program from IAIN Ponorogo. The survey research method was conducted to determine the profile of studentsâ€™ views on the NOS and science education. Respondents who filled out the research questionnaire were 102 students. Based on the survey results, the VOSE profile was obtained that the Science-Physics students had difficulty conceptualizing the general picture of VOSE because in some aspects of NOS it appeared that students experienced confusion.Science-Physics students have a positive attitude towards teaching NOS in terms of tentativeness, aspect of the nature of observation, as well as aspect of theory and law.However, Science-Physics students have negative attitudes towards teaching NOS in the aspect of the scientific method. Thus, the implication of this research requires that Science-Physics students learn and further research about the concept of NOS in order to have a correct understanding.  DOI: 10.29408/kpj.v4i2.2873